Operation free Iraq: a gendered content analysis of newspapers - Jepson, Niki; Davis, Tricia (My University, 2005)
Women have been historical underrepresented in the field of journalism, and it is journalists we mostly rely upon when hearing information concerning war. With the gendered imbalance that exists in journalism, it leads us to question whether we are getting a full picture of what is happening in the war-field. A content analysis of three major newspapers was conducted to investigate: Do men and women write differently from the war field? If they do, what are the consequences of the gender inequality that exists? And, how might a gender-imbalanced reporting structure shape the public?s perception about war?
Color poster with text detailing research conducted by Niki Jepson and Dr. Tricia Davis (University of Wisconsin-River Falls) that examines how male and female journalists write about war.
Keywords: Women in journalism; War reporting; Journalism; Women journalists; Female journalists; Journalism--Sex differences; Male journalists; Journalism and gender; War correspondents